2010
DOI: 10.1002/ajhb.21079
|View full text |Cite
|
Sign up to set email alerts
|

Responsiveness of the reproductive axis to a single missed evening meal in young adult males

Abstract: Objectives The male reproductive axis is responsive to energetic deficits, including multi-day fasts, but little is known about brief periods of fasting (<24 hours). Reduced testosterone in low-energy balance situations is hypothesized to reflect redirection of resources from reproduction to survival. This study tests the hypothesis that testosterone levels decrease during a minor caloric deficiency by assessing the effects of a single missed (evening) meal on morning testosterone in 23 healthy male participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 57 publications
1
37
0
Order By: Relevance
“…(a) Tsimane -United States salivary testosterone comparison Tsimane pre-competition saliva specimens (n ¼ 82) were compared with age-matched US saliva specimens (n ¼ 40) collected as controls during a non-competition study [27] to establish differences in baseline T levels. Tsimane male salivary T (182.9 pg ml No single position (forward, midfielder, defender, goalkeeper) had a statistically different T response when compared with other positions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(a) Tsimane -United States salivary testosterone comparison Tsimane pre-competition saliva specimens (n ¼ 82) were compared with age-matched US saliva specimens (n ¼ 40) collected as controls during a non-competition study [27] to establish differences in baseline T levels. Tsimane male salivary T (182.9 pg ml No single position (forward, midfielder, defender, goalkeeper) had a statistically different T response when compared with other positions.…”
Section: Resultsmentioning
confidence: 99%
“…Saliva exhibiting blood contamination (n ¼ 22 specimens) [34], or inadequate volume (n ¼ 5 specimens) were excluded, leaving a total of 237 usable specimens from 82 individuals. Salivary T was measured via an in-house enzyme immunoassay [27] that cross-reacts 100 per cent with T, 57.4 per cent with 5-a-dihydrotestosterone, 0.27 per cent with androstenodione and less than 0.05 per cent with other androgens [35]. Specimens were run in duplicate, with each participant's samples run on the same plate to reduce bias owing to inter-plate variation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…, for instance, demonstrated that Honduran men upon diagnosis with malaria had lower testosterone than an uninfected comparison group, but that patients" testosterone rose steadily until equal to the comparison group over eight days of treatment with anti-malarial drugs. Likewise, other studies have reported declines in men"s testosterone after influenza vaccination (Simmons & Roney, 2009) and the day after missing only a single evening meal (Trumble et al, 2010).…”
Section: Accepted Manuscriptmentioning
confidence: 97%
“…Males in better condition can afford higher levels of testosterone and the associated physiological costs; thus there is a wide range of testosterone levels within and between individuals [86,87]. Males in poor condition cannot maintain high levels of testosterone; illness and injury lead to rapid decreases in testosterone [88 -90], as does short and longer term fasting [91,92], and extensive energetic expenditure [93]. While some human and chimpanzee populations show no seasonal variation in testosterone [94,95], large studies of subsistence human and wild baboon populations report decreases in testosterone during leaner times [96,97].…”
Section: Testosterone Competition and Paternal Investmentmentioning
confidence: 99%